Views of Students of ASPAITE Athens on the Connection between Theory and Practice in the Context of their Microteaching (Global Journal of Human-Social Science, 2023)
The present article aims to highlight how the pedagogical courses - specifically those of Teaching Methodology and Educational Evaluation - taught to students of ASPAITE Athens in previous semesters helped them to plan organize and implement the microteaching courses they are asked to implement in later semesters
Keywords: microteaching; teaching methodology; educational evaluation; theory-practice